The worrisome wombat - Scarffe, Bronwen (Nelson Melbourne, 1994)
"The Worrisome Wombat" by Bronwen Scarffe is a delightful children's book that explores the adventures of a wombat named Wally. Wally is a lovable but anxious wombat who constantly frets about various aspects of his life, from the safety of his burrow to the weather and everything in between. The story follows Wally as he navigates his fears and insecurities with the help of his friends in the forest. As Wally's friends support and encourage him, he gradually learns to manage his worries and embrace a more positive outlook. Through engaging illustrations and a heartwarming narrative, the book addresses important themes such as resilience, the value of friendship, and the ability to overcome personal fears. "The Worrisome Wombat" is both entertaining and educational, offering young readers a comforting message about dealing with anxiety and the importance of leaning on loved ones for support.